Evaluation of MoveSmart MS - an online structured exercise, Social Cognitive Theory-based behavioural coaching and peer support programme - on anxiety in multiple sclerosis - Austin Fahy; Susan Coote; Rebecca Maguire (PLoS ONE, 2025)
Background Anxiety is a common experience among people with multiple sclerosis (PwMS). While it is known that engaging in exercise has a number of benefits, the role played by exercise in reducing anxiety has received less attention in this context. Understanding the effect of exercise on anxiety, the predictors of this change. and participant experiences will help to further develop programmes which can support PwMS. Aim This study used a pre/post evaluation design (1) to assess the efficacy of a structured physiotherapist-led online exercise programme (MoveSmart) on anxiety in PwMS living in Ireland, (2) to identify the role of sociodemographic, health and psychological factors in predicting baseline anxiety, (3) to investigate how changes in these factors predict changes anxiety following completion of the programme, and (4) to explore the experiences of participants with the programme. Method Data from 284 PwMS who took part in a 10-week programme between January 2021 and June 2022 were analysed. Participants provided sociodemographic and health information at baseline and completed measures of psychological factors at baseline and again on completion of the programme. Change in anxiety scores were analysed using hierarchical regression analysis. Follow-up focus groups were conducted with 25 participants to explore their experiences of taking part in the programme, with data analysed using reflexive thematic analysis. Results Participation in the MoveSmart programme was associated with significant reductions in anxiety. Younger age, lower disability, higher Multiple Sclerosis Impact Scale-29 physical scores and higher fatigue were significantly associated with higher baseline anxiety scores, and changes in the physical impact of MS predicted changes in anxiety scores. Key themes identified through thematic analysis included ‘Benefits of peer support’, ‘Benefits of goal setting’, ‘Noticed improvements’ and ‘Praise for programme execution’. Conclusion Participation in a physiotherapist-led structured exercise programme resulted in significant improvements in anxiety, in part through reducing the impact of physical MS symptoms. Qualitative results suggest that peer support and goal-related coaching may have contributed to reductions in anxiety.